PERBEDAAN KEPUASAN RADIO KONVENSIONAL DENGAN STREAMING (STUDI DESKRIPTIF KUANTITATIF TENTANG GRATIFIKASI SOUGHT DAN GRATIFIKASI OBTAINED PADA RADIO ELFARA MALANG) - Tanjung, Intan Septiana; Kriyantono, Rachmat; Sujoko, Anang (Faculty of SociaI and Political Sciences (FISIP), Universitas Islam Negeri (UIN) Bandung, 2019)
Radio is one of the mainstream media with many listeners around the world. Technological developments have spurred the media economy to innovate so that it is not only used in conventional frequencies, and it is now available in the form of streaming. Elfara FM Radio was chosen as an empirical phenomenon because it has an alternative media in the form of a website for streaming services on www.radioelfara.com and primetime programs that are the choice of researchers is Hitzteria (at 14.00-18.00). This study aims to determine the differences in the level of satisfaction of listeners of the Hitzteria program through conventional media or streaming media on Elfara FM radio. Through quantitative methods, researchers will try to find differences in the level of satisfaction through the technique of data collection, namely the questionnaire on Radio Elfara. The researcher used the MAIN model to test the hypothesis, which consisted of Modality, Agency, Interactivity, and Navigability. The results of the study will be very useful for the development of communication science studies, especially the study of economic media and intestinal gratification.